Calibration of microsimulation model for tight urban diamond interchange under heterogeneous traffic. (May 2019) - Azam, M.; Puan, O. C.; Hassan, S. A.; Mashros, N.
Abstract: Traffic simulation models have been widely used to evaluate design alternatives and to help decision-makers to select best design option for prevailing traffic conditions. This study focuses on application of microsimulation model to the performance assessment of Tight Urban Diamond Interchange (TUDI) located in a congested urban setting with population more than 9 million and current transport demand up to 13.5 million daily motorized trips. Geometric and operational data was collected by conducting multiple site visits. Traffic volume data showed the heterogeneous nature of traffic. Microsimulation model; VISSIM was applied and appropriateness of this model and the proposed methodology was assessed based on maximum queue length as Measure of Effectiveness (MOE). Calibration of model was done in two stages: system calibration and operational calibration. System calibration was done by reflecting the actual geometric and control conditions in model. While operational calibration was done by conducting Sensitivity Analysis (SA). MOE values from calibrated model were compared with the field values of maximum queue length. This study revealed that SA helps in selecting the most appropriate parameters and their values. Results from VISSIM show the cumulative difference of 32 % from the field observed values.